Developing web application and hybrid application; How developing for different platforms differentiated and how users experienced these - Tenkanen, Teemu (My University, 2022)
The mobile application development process is evolving rapidly, and new frameworks are created every month. When choosing how to develop mobile application, there are three main development platforms: web application, native application, and hybrid application. These all have their positives and negatives, and they all have their own strengths when chosen for right kind of project. Previous research has been conducted but they have mixed results when comparing. Thus, this research was made to investigate more closely how the development process for web application and hybrid application differentiated and how the end product applications differentiated, when analysing the experiences of the users. Two applications were developed during this research: React.js application for web development and React Native for hybrid development. To analyse users experience, web and hybrid versions of the same application was given to the participants. First the participants were asked to test the main functionalities of the application, and after testing answering the survey. The survey tried to ask how positive or negative some of the features of the applications were. In conclusion, the study shows that the hybrid application version was superior. In the survey hybrid application had slightly more positive answers and was clearly faster version of the two. The development process for the web application was easier and had better options for choosing the best suitable tools and libraries.

Mobiilisovellusten ohjelmointi prosessit kehittyvät nopeasti, ja uusia ohjelmointityökaluja julkaistaan joka kuukausi. Mobiilisovelluksen kehittämistä valittaessa on kolme pääkehitysalustaa: verkko-, natiivi- ja hybridisovellus. Näillä kaikilla on positiiviset ja negatiiviset puolensa, sekä omat vahvuutensa, kun ne valitaan oikeanlaiseen projektiin. Aikaisempia tutkimuksia on tehty, mutta näiden tulokset ovat ristiriitaisia. Näin ollen tämä tutkimus tehtiin tarkentamaan, miten verkko- ja hybridisovelluksen kehitysprosessi eroavat ja miten lopputuotteet erottuivat käyttäjien kokemuksia analysoitaessa. Tämän tutkimuksen aikana kehitettiin kaksi sovellusta: React.js - sovellus verkkokehitykseen ja React Native hybridikehitykseen. Käyttäjäkokemuksen analysoimiseksi osallistujille annettiin samasta sovelluksesta verkko- ja hybridiversiot. Ensin osallistujia pyydettiin testaamaan sovelluksen päätoimintoja ja testauksen jälkeen vastaamaan kyselyyn. Kyselyn tavoite oli mitata, kuinka positiivisia tai negatiivisia jotkin sovellusten ominaisuudet olivat. Tutkimus osoitti, että hybridisovellusversio oli parempi kuin verkkosovellusversio. Kyselyssä hybridisovellus sai hieman enemmän myönteisiä vastauksia ja oli selvästi nopeampi versio näistä kahdesta. Verkkosovelluksen kehitysprosessi oli helpompaa ja siinä oli paremmat mahdollisuudet valita sopivimmat työkalut ja kirjastot.
Keywords: React, React Native, Mobile application, Development platforms, Hybrid application, Web application